2016
DOI: 10.1093/mnras/stw2400
|View full text |Cite
|
Sign up to set email alerts
|

The surface roughness of (433) Eros as measured by thermal-infrared beaming

Abstract: In planetary science, surface roughness is regarded to be a measure of surface irregularity at small spatial scales, and causes the thermal-infrared beaming effect (i.e. re-radiation of absorbed sunlight back towards to the Sun). Typically, surface roughness exhibits a degeneracy with thermal inertia when thermophysical models are fitted to disc-integrated thermal-infrared observations of asteroids because of this effect. In this work, it is demonstrated how surface roughness can be constrained for near-Earth … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 43 publications
3
18
0
Order By: Relevance
“…This roughness is comparable to that of other asteroids [43][44][45][46] but rougher than that of the Moon [47]. The model itself does not set a spatial scale for this roughness; it can be anywhere between the resolution of the shape model used for the thermal analysis (~12 m) and the diurnal thermal skin depth (~2 cm, methods), though we expect that roughness at the smaller length scales dominates the thermal signature [43]. From the shape model of Bennu [3], we find RMS slopes that increase with decreasing spatial scale.…”
Section: Evidence Of Particulate Regolithsupporting
confidence: 80%
See 1 more Smart Citation
“…This roughness is comparable to that of other asteroids [43][44][45][46] but rougher than that of the Moon [47]. The model itself does not set a spatial scale for this roughness; it can be anywhere between the resolution of the shape model used for the thermal analysis (~12 m) and the diurnal thermal skin depth (~2 cm, methods), though we expect that roughness at the smaller length scales dominates the thermal signature [43]. From the shape model of Bennu [3], we find RMS slopes that increase with decreasing spatial scale.…”
Section: Evidence Of Particulate Regolithsupporting
confidence: 80%
“…These results suggest that the thermal infrared beaming is most sensitive to the smaller end of the spatial scale (i.e., close to the thermal skin depth), and that Bennu is much rougher at these scales than at larger spatial scales. See [43] for more discussion of thermal infrared roughness.…”
Section: Corresponding Authorsmentioning
confidence: 99%
“…Figure 1(b) shows thermal phase curves of objects with smooth and rough surfaces of varying thermal inertia. Figure 1(c) shows the thermal flux emitted as a function of sub-solar latitude and recreates the findings of Rozitis (2017). In general, the surface roughness of airless bodies are more easily estimated near opposition or, better yet, with disk-resolved observations that offer a greater range of viewing geometries.…”
Section: Thermal Inertia and Surface Roughnesssupporting
confidence: 57%
“…In general, the surface roughness of airless bodies are more easily estimated near opposition or, better yet, with disk-resolved observations that offer a greater range of viewing geometries. The Rozitis (2017) study shows that the uncertainty in thermal inertia is slightly larger for an object observed at a large phase angle, as a consequence of the difficulty in estimating surface roughness. c Figure 1: Comparison of thermal flux emitted from an object varying it's thermophysical properties and shape, as a computed from the TPM described in section 3.…”
Section: Thermal Inertia and Surface Roughnessmentioning
confidence: 88%
“…Regarding future improvements on the TPM, it should happen based on studying the very few targets with ground-truth knowledge of physical properties and rich (thermal) data sets (e.g., Rozitis 2017). Or maybe with thermal infrared data from spacecraft missions (OSIRIS-REx data, Lauretta et al 2015).…”
Section: Discussionmentioning
confidence: 99%